2021
DOI: 10.1111/exd.14497
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA profiling of psoriatic skin identifies 11 miRNAs associated with disease severity

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri bution-NonCo mmercial License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited and is not used for commercial purposes.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 78 publications
(167 reference statements)
0
8
1
Order By: Relevance
“…MiRNAs play crucial roles in various cellular processes and have been implicated in psoriasis pathogenesis. [7][8][9][10]14 Skin tissue collection by punch-biopsy method is extremely painful and in- individuals can serve as disease detection and progression markers. Psoriasis is characterized by a complex interplay of different cell types including epidermal keratinocytes, dermal fibroblasts and infiltrating immune cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…MiRNAs play crucial roles in various cellular processes and have been implicated in psoriasis pathogenesis. [7][8][9][10]14 Skin tissue collection by punch-biopsy method is extremely painful and in- individuals can serve as disease detection and progression markers. Psoriasis is characterized by a complex interplay of different cell types including epidermal keratinocytes, dermal fibroblasts and infiltrating immune cells.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from various genetic susceptibility factors, the contribution of epigenetic regulations by DNA methylation and miRNA deregulation among others have also been reported in the literature. 1,[4][5][6][7][8][9][10] MiRNAs play a crucial role in regulating various biological processes including cell proliferation, differentiation and signal transduction. [11][12][13] Deregulations of miRNAs and their potential to be used as a biomarker for disease diagnosis and progression have been studied in many diseases including psoriasis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…microRNAs (miRNAs) are small non-coding RNA molecules able to post-transcriptionally modulate gene expression, and to contribute to the development or regulation of several diseases, including skin inflammation 11 . Only few studies have aimed to describe miRNA expression profiles in the skin of AD patients 12 , 13 , while multiple studies have been performed for PV 14 16 . Moreover, to our knowledge, only the earliest study from 2007 compared miRNA profiles of AD and PV skin, and indicated both similarities and differences between these two diseases 17 .…”
Section: Introductionmentioning
confidence: 99%
“…From a clinical perspective, miRNAs have been intensively studied in various human diseases such as cancers, metabolic disorders, infectious diseases, and immunological disorders as biomarkers and therapeutic targets 20 . The pathologies modulated by miRNAs have been examined in dermatologic diseases such as psoriasis [21][22][23] , atopic dermatitis 24 , and allergic contact dermatitis 25,26 . However, little is known about the roles of miRNAs in SD.…”
mentioning
confidence: 99%